A study of pre-sequences in announcements in English versus vietnamese - Lê Thị Phương (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Pre-sequences are popular phenomena in human process of communication and widely employed for many speech acts. This research offers an analysis of pre-sequences in announcements in English and Vietnamese. The study aims at examining pre-sequences in announcements and finding out similarities and differences of pre-announcements in English and Vietnamese. Besides, the study also suggests some implications of finding for teaching and learning English as a foreign language in Vietnam. The study focuses on the investigation of the syntactic and pragmatic features of pre-sequences in announcements in English and Vietnamese based on the analysis of the data collected from English and Vietnamese conversational books, short stories and novels.